2010
DOI: 10.1128/jb.00382-10
|View full text |Cite
|
Sign up to set email alerts
|

The LysR-Type Transcriptional Regulator QseD Alters Type Three Secretion in Enterohemorrhagic Escherichia coli and Motility in K-12 Escherichia coli

Abstract: Enterohemorrhagic Escherichia coli (EHEC) O157:H7 responds to the host-produced epinephrine and norepinephrine, and bacterially produced autoinducer 3 (AI-3), through two-component systems. Further integration of multiple regulatory signaling networks, involving regulators such as the LysR-type transcriptional regulator (LTTR) QseA, promotes effective regulation of virulence factors. These include the production of flagella, a phage-encoded Shiga toxin, and genes within the locus of enterocyte effacement (LEE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 86 publications
0
20
1
1
Order By: Relevance
“…Here, we identified E. coli YjiE as the first transcription factor specifically protecting cells from HOCl-derived killing. YjiE was described recently as cell density-dependent motility repressor, QseD (33). However, in this work, we did not observe an effect of YjiE on the motility of various E. coli strains (data not shown).…”
Section: Discussioncontrasting
confidence: 63%
“…Here, we identified E. coli YjiE as the first transcription factor specifically protecting cells from HOCl-derived killing. YjiE was described recently as cell density-dependent motility repressor, QseD (33). However, in this work, we did not observe an effect of YjiE on the motility of various E. coli strains (data not shown).…”
Section: Discussioncontrasting
confidence: 63%
“…Thus, significant but low levels of increases in the transcriptional levels of LEEcarried ler and espA, observed in the qseBC mutant irrespective of the presence or lack thereof of NE, could be instrumental in imparting a competitive edge to the mutant relative to the parent strain in intestinal colonization of calves. The transcriptional levels of ler, which encodes Ler for the positive regulation of LEE, are controlled by several known negative and positive transcriptional factors, including QseA and QseD, whose expression is also modulated in response to quorum-sensing signaling (30,(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Domain structure analysis revealed that both Z0342 and OvrB contain an N-terminal DNA-binding helix-turn-helix (HTH) motif and a C-terminal co-inducer-binding domain, which are conserved in the LysR-type transcriptional regulator (LTTR) family (Figure 1(b)). LTTRs regulate a variety of virulence determinants and are global regulators of pathogenicity in many bacterial pathogens [29]. Z0343 contains an adh_short superfamily domain, which is the active site of formaldehyde dehydrogenase; thus, Z0343 may be involved in metabolizing endogenous and exogenous aldehydes (Figure 1(b)).…”
Section: Resultsmentioning
confidence: 99%